AN INTEGRATED THREE-FLOW APPROACH FOR FRONT-END SERVICE COMPOSITION - Lim, Mei Ting; Su, Moon Ting (Malaysian Journal of Computer Science, 2019)
End-User Service Composition (EUSC) aims to enable end-user programmers who are not professional developers develop applications by composing or aggregating existing web services. Despite the effort, studies have shown that, end-user programmers are not able to deal with the technical complexities involved in EUSC. One way to deal with this issue is Front-End Service Composition (FESC), which allows end-user programmers to compose web services at the presentation layer of an application by configuring user interface (UI) widgets that represent the back-end web services. However, there are not many studies on FESC and the existing ones suffer two main problems, namely, lack of control flow and/or application flow visualization, and they still require end-user programmers to have certain technical knowledge in the service composition process that these end-user programmers generally do not possess. Following that, this study proposes an integrated three-flow approach (application flow, control flow and data flow) to deal with the current limitations of FESC. The approach generates the GUI of web services automatically, thus allowing the UI of the application to be developed at the same time the required web services are assembled. The approach allows end-user programmers to explicitly configure the three different types of flows involved in service composition. A proof-of-concept prototype, QuickWSC, that incorporates the three-flow approach was developed. It adopts a side-by-side multiple-view design to support visual configuration of the three flows in an uncluttered yet synchronized manner that adhered to established design guidelines. A user evaluation study was conducted on QuickWSC. The results show that it is easy to compose web services by explicitly specifying the three flows, that the configurations of the three flows integrated in the two views helps in composing application from web services, and that no technical knowledge is required to use QuickWSC